PERANCANGAN ULANG TATA LETAK PABRIK TAHU KHARISMA - Paramita, Melanda; Susanti, Elva (Computer Science and Industrial Engineering, 2021)
A poor layout causes a poor process flow pattern, this happens to the tofu kharisma factory because it has not taken into account the degree of proximity between work stations in accordance with the flow of the production process. which greatly affects the distance of material handling. A new layout was redesigned to rearrange the material flow according to the product flow. To improve the layout of the work station, this study used the From to Chart, Activity Relationship Chart (ARC) method which was applied to the Blocplan90 algorithm. Based on the blocplan90 algorithm, the best layout of the 5 alternative choices is in layout 1. The total distance in the initial layout is 13,860 m while in the proposed layout it is 12,054 m. So, the total distance reduction is 1,806 m/month. MH cost in the initial layout is Rp. 7,193,340/month, while the MH cost for the proposed layout is Rp. 6,256,026/month. So, the total decrease in MH cost is Rp. 937,314/month and the total initial distance and final distance that has been obtained is the percentage efficiency of 13.03%/month.